Original paperThe effect of clary sage oil on staphylococci responsible for wound infections - Sienkiewicz, Monika; Głowacka, Anna; Poznańska-Kurowska, Katarzyna; Kaszuba, Andrzej; Urbaniak, Anna; Kowalczyk, Edward (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : The spreading of bacterial antibiotic resistance among clinical strains of pathogenic bacteria has made investigators to search for other active antibacterial agents which could provide a valuable complement to the existing therapies. Aim: To determine the antibacterial activity of clary sage oil (Salvia sclarea L.) against Staphylococcus clinical strains which were isolated from patients with wound infections. Material and methods : A comprehensive evaluation of Staphylococcus clinical strain resistance to antibiotics was performed. The constituents of clary sage oil were assayed by GC-FID-MS analysis. The minimal inhibitory concentration (MIC) of the tested essential oil against staphylococci by the micro-dilution broth method was determined. Results : The clary sage oil was active against Staphylococcus aureus, S. epidermidis and S. xylosus with MIC values ranging from 3.75 to 7.00 µl/ml. Conclusions : The results of the in vitro tests encourage to use formulations containing sage oil as the active natural antimicrobial agent. Because of its antimicrobial properties clary sage oil may be applied to treat wounds and skin infections.